The Impact of Multilingualism on Language Policy and Instruction in Higher Education Institutions - Laila Kumana; Jonah Rasi; Mereani Tane (International Journal of Multilingual Education and Applied Linguistics, 2024)
This article examines the influence of multilingualism on language policies and instructional practices in higher education institutions across different countries. The study investigates how universities integrate multiple languages into their curricula, support bilingual students, and adapt teaching methods to accommodate linguistic diversity. The findings suggest that a multilingual approach in higher education can promote inclusivity, enhance student engagement, and contribute to the global competitiveness of institutions.Keywords: , , , ,